MODEL KOMPETENSI DIGITAL MAHASISWA DALAM SISTEM PEMBELAJARAN JARAK JAUH - ' Novrianti, Darmansyah, Fetri Yeni (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
This article presents the development of a digital competency model for Distance Learning (DL) students in Indonesia which is also called CompDigAl_EAD. The following topics were discussed in this study: educational competence, digital competence, and students in distance learning. This model was developed between 2015 and 2020. It was created based on theoretical reference and competency mapping in two classes, one of which was a distance learning undergraduate program and the other a postgraduate program, to enroll students' digital competencies in this modality. As a result, a set of competencies is obtained. It is analyzed by DL students and specialists. Based on the results, the model consists of seven general competencies: 1. Computer use, 2. Internet and online communication, 3. Communication, 4. Information management, 5. Digital content creation and development, 6. Management virtual profiles and, 7. Attendance On line. Currently, this model is in the final validation stage. The aim is that research results will support students and professors in the development of digital competences in DL modality. Keywords: Digital Competence, Distance Learning, Distance Learning